Optimalisasi Peran Badan Usaha Milik Negara (BUMN) pada Era Masyarakat Ekonomi Asean (MEA) - Ikhwansyah, Isis; Chandrawulan, An An; Amalia, Prita (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
ASEAN Economic Community (AEC) which came into effect since 2015 requires the creativity of the Indonesian society in competing with other ASEAN countries. One of the necessary strategies in dealing with AEC is to optimize the role of the State-Owned Enterprises (BUMN). With regards to the implementation of the AEC, it is important to provide adequate regulation in order to ensure legal certainty for BUMN. The main purpose of this research is to discover form of national regulation that can maximize business opportunity for BUMN in AEC era. It is found that the existing regulations have not yet given business opportunity for BUMN in AEC era. The existing regulations are contradictory one to another especially relating to the status of the state finance inserted as capital into BUMN. In addition, the Constitutional Court decision Number 48/PUU-XI/2013 maintained that the capital inserted into BUMN is considered as part of the state finance. Therefore, this brings about fundamental impact on future cases since the nature of the Constitutional Court decision is erga omnes.